Changes in Blood Profile from Steady State in Patients with Sickle Cell Anemia Admitted for Vaso-occlusive Crisis and Acute Chest Syndrome. (25th August 2020) - Klouda, Timothy; Raybagkar, Deepti; Bernstein, Bruce; Apollonsky, Nataly
Abstract : Close to half of all patients with sickle cell disease (SCD) will have at least one episode of acute chest syndrome (ACS) during their lifetime. Multiple cells and molecules involved with the inflammatory cascade play a role in the development of ACS. We found that patients with SCD who developed ACS as a complication of a vaso-occlusive crisis (VOC) had a significant increase in leukocytes and decrease in platelets from their steady state when compared with a separate admission for VOC without ACS development. No significant change from steady state hemoglobin or reticulocyte count was noted between the two admissions. These results indicate that trending laboratory markers may be useful to predict patients at risk for ACS development.